Wireless remote sensor on iOS device - Zhu, Qinglei (2016)
Oscilloscope is an essential scientific and engineering equipment in measuring signal strength, frequencies, periods and other significant parameters. In traditional settings, oscilloscopes are installed in the laboratory. The initial acquiring cost could be high and thus become unaffordable to individual users. Though itself has evolved from analog based operation to highly advanced digital technology, it is still unable to meet engineer’s demand for a mobile and cost- effective oscilloscope device. This project is to address such needs to develop a prototype of mobile oscilloscope. By replacing traditional bulky and heavy stationary equipment with latest mobile computing device---iPad, the trade-off of some level of accuracy to much greater portability is highly recommended. In this project, iPad substitutes oscilloscope panels and screens as the integrated virtual panel and display. The oscilloscope configuration and result presentation could be simultaneously achieved on single iPad screen, brings a superb level of control and feedback. The traditional probe is substituted by another iOS device, most likely iPhone as input source. The raw data captured from input sources is firstly pre- processed and transmitted wirelessly to the hosting iPad for further analysis. The host device will take in the received signal and apply filtering and processing mechanism before finally demonstrating the results on the screen. The outcome of this project is encouraging as the prototype system well demonstrates the initial design and construction. The application on iPad is successfully built with original goal achieved. At the end of this project, future research directions have been identified for next batch of researchers or students who continue working on the concept of mobile oscilloscope.